"Like Oil and Water": Adaptation as Textuality, Intertextuality, and Metatextuality in Lady Snowblood (Fujita, 1973) - Matthew Bolton (Studies in 20th & 21st Century Literature, 2017)
Toshiya Fujita’s 1973 film adaptation of Kazuo Koike and Kazue Kamimura’s manga series Lady Snowblood is a case study in the challenges inherent in adapting a complex graphic narrative to film. A sprawling episodic story of assassination and revenge, the original manga text offers challenges to any adapter in terms of content, form, narrative construction, and media affordances, challenges that Fujita and his screenwriter Norio Osada gamely take up in their film. In their attempts to adapt their source material, Fujita and Osada rely on three adaptation strategies—textuality, intertextuality, and metatextuality—that reveal both their nimble thinking about adaptation as an aesthetic process, but that also demonstrates the limitations of these strategies for containing and assimilating the capacious source material upon which the film is based. Ultimately, Fujita’s film is a fascinating text that both reworks and revises its source material while also allowing it to remain a legible contesting presence within its own narrative.
Keywords: adaptation; manga; Lady Snowblood; jidaigeki; metatextuality; intertextuality